Are you addicted to Candy Crush Saga? An exploratory study linking psychological factors to mobile social game addiction. Issue 4 (November 2016) - Chen, Cheng; Leung, Louis
Highlights: 7.3% of Candy Crush Saga players in the study sample were considered addicts in China. Addicts were characterized as lonely, leisurely bored, and motivated by mobility of the game. Frequent players had a higher tendency to become addicts. Loneliness and self-control were significant predictors of mobile social game addiction. Leisure boredom was significantly linked to the intensity of game use. Abstract: The purpose of this study is to explore the relation of psychological factors (including perceived gratifications, loneliness, leisure boredom, and self-control) to mobile social game use and addiction. The study data were gathered from 409 respondents in China. The exploratory factor analysis yielded a gratification structure of five factors (mobility, entertainment, sociability, achievement, and relaxation). According toYoung's (1998) classic definition, 7.3% of the participants in the study sample were considered addicts. They were characterized as lonely, leisurely bored, and motivated by the mobile nature of the game. As expected, frequent players had a higher tendency to become addicts. In particular, loneliness and self-control were significant predictors of mobile social game addiction, whereas leisure boredom was linked to the intensity of game use. The limitations of the study and its implications for future research are discussed.